A novel solar-geothermal system integrated with earth–to–air heat exchanger and solar air heater with phase change material—numerical modelling, experimental calibration and parametrical analysis. (March 2021) - Qin, Di; Liu, Jiang; Zhang, Guoqiang
Abstract: In order to compensate drawbacks of traditional earth–to–air heat exchanger (EAHE) system, such as the unstable outlet air temperature, the overheating and the limited operation period, a novel coupled system systematically integrating an EAHE and a solar air heater (SAH) with phase change material (PCM), was proposed in this study. The complementary between geothermal and solar energy is exploited and served for building energy savings. On-site experimental testing and enthalpy-based numerical modelling using the control volume method were conducted for thermal and energy performances prediction. Systematic and parametrical analyses have been conducted using the developed mathematical model to investigate the effects of critical parameters on the thermal and energy performances. Our findings illustrate that the implementation of PCM can effectively stabilize the outlet air temperature for nearly 4.5 h and prolong the working period to 24 h. Due to the heat transfer enhancement, the increase of the airflow rate can significantly increase the system heating capacity, whereas the outlet air temperature is decreased with a maximum magnitude of 5.3 °C. Furthermore, the diurnal thermal performance of the system is highly dependent on the phase change temperature, whereas the time-duration of the effective operation is highly dependent on the PCM latent heat. Moreover, the system nocturnal thermal behavior can be improved with the increase of the PCM thermal conductivity, whereas a saturated improvement can be noticed when the PCM thermal conductivity is 1.0 W/(m·K). This study proposes a complementary geothermal and solar energy system, together with phase change material for the performance stability improvement, which are important for the promotion of green buildings with energy-efficient utilization of geothermal and solar energy. Highlights: Heat transfer mechanism of an integrated geothermal and solar energy system with phase change material. The peak outlet air temperature and the heating capacity fluctuation were decreased by 8 °C and 38.1%, respectively. Outlet air temperature can be stabilized for 4.5 h and working period can be prolonged to 24 h. Heating capacity deviation is 12.9% for cases with different latent heat of PCM at 160 and 220 kJ/kg. Optimal design and robust operation through multivariant parametric analysis.